On the moral necessity of tort law: the fairness argument - Steel, S (Oxford University Press, 2020)
Various theorists have claimed that by prohibiting certain responses to violations of rights by legal subjects, the legal system owes legal subjects something in return, and that something should take the form of tort law. My overall claim is that the best version of this ‘fairness argument’ for a duty to provide tort law is of limited success. The fairness argument, at best, shows that legal systems are under a pro tanto duty to provide only a highly limited form of tort law. The article first seeks to articulate the most powerful version of the fairness argument. It then argues, through consideration of four objections, that the argument justifies at best a pro tanto duty to provide a highly limited form of tort law, if it justifies a duty to provide tort law at all.